2018
DOI: 10.1111/1744-7941.12186
|View full text |Cite
|
Sign up to set email alerts
|

Fostering workplace creativity: examining the roles of job design and organizational context

Abstract: This study investigates the actor–context interaction effects of job characteristics and organizational context on individual creativity in the South Korean context. Specifically, we examined the relationship among three job characteristics (i.e. skill variety, autonomy and feedback), three organizational context factors (i.e. organizational climate, resources and extrinsic rewards), and individual creativity. Our findings indicated that all job characteristics positively affected individual creativity. Only e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The underlying logic is that even though employees have proactive characteristics, their motivation to act proactively depends on contextual factors that either support or discourage them (Grant and Ashford, 2008). Although creativity research provided a theoretical basis for examining contextual factors (Anderson et al , 2014; Yoo et al , 2019; Zhou and Hoever, 2014), literature on employee proactivity–creativity relationship lacks evidence on climate-related determinants. Therefore, addressing this limited understanding, we suggested that an initiative climate might be one of the key determinants in enacting proactive behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying logic is that even though employees have proactive characteristics, their motivation to act proactively depends on contextual factors that either support or discourage them (Grant and Ashford, 2008). Although creativity research provided a theoretical basis for examining contextual factors (Anderson et al , 2014; Yoo et al , 2019; Zhou and Hoever, 2014), literature on employee proactivity–creativity relationship lacks evidence on climate-related determinants. Therefore, addressing this limited understanding, we suggested that an initiative climate might be one of the key determinants in enacting proactive behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Creativity enables organisations to generate novel and useful ideas that help improve work processes, offer solutions for the problems or proactively develop strategies for innovative expectations (Shalley et al , 2004). In this context, the question of how organisations design the work for the employees to reveal their creative potential has gained importance (Yoo et al , 2019). Although the early views on job design proposed that top-down managerial initiatives enhance individual and organisational effectiveness, the evolving perspectives have emphasised that the self-initiated proactive behaviours better suit intrinsic needs and help enhance employee motivation and performance (Grant and Parker, 2009; Oldham and Hackman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Using a variety of skills (X3) gives workers the opportunity to use their knowledge and experience (Ling and Wong, 2016), which leads to their ability to use resources efficiently. The broad skill structure within the job enables FMs to achieve higher levels of creativity (Yoo et al , 2019), leading to better resource utilisation.…”
Section: Discussion On the Association Between Work Outcomes And Job Situational Factorsmentioning
confidence: 99%
“…Based on motivator-hygiene theory, job design consists of five core motivational characteristics (Hackman & Oldham, 1976). Specifically, skill variety refers to the degree of use of different skills when conducting the work (Yoo et al, 2019). Task identity refers to the opportunity to complete a whole and identifiable piece of work (Catherine, 2018).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%